Field researcher guide: Gender-responsive study of phage adoption opportunities for chicken keepers in Kenya - Campbell, Zoë A.; Njiru, Nelly M. (International Livestock Research Institute, 2022)
The objective of this research activity is to assess the feasibility of adoption of bacteriophage (phage) technology by chicken keepers in backyard and commercial production systems in Kenya and to identify opportunities and barriers to adoption that may vary by gender. Phages are parasitic viruses that can be used to attack bacteria that cause illness in poultry and people, in this case, Salmonella strains that cause salmonellosis, fowl typhoid, and pullorum disease in chickens and diarrhoeal diseases in people. Current methods of controlling Salmonella infections in poultry farms, either for therapeutic or prevention, include the use of antibiotics, and antimicrobial resistance (AMR) is a growing concern.